Climate-Induced Expansion of Consumers in Seagrass Ecosystems: Lessons From Invasion Ecology - Martin, Charles W.; Valentine, John F. (Frontiers in Marine Science, 2022)
A warming climate is driving the poleward expansion of tropical, subtropical, and temperate plant and animal distributions. These changes have and continue to lead to the colonization of novel organisms into areas beyond their historical ranges. While the full scope of ecological impacts remains unclear, these expansions could alter density-dependent interactions, habitat occupancy patterns, and food web dynamics– similar to exotic species impacts in invaded ecosystems. Seagrasses are habitats of particular interest, given their widespread distribution and ecosystem services. While multiple recent studies report on the effects of the return of larger tropical herbivores in seagrass beds in warming subtropical waters, less is known about the addition of mid-trophic level consumers. These consumers are often key determinants of energy and nutrient transfers from basal resources to higher order predators. Here, we discuss the potential impacts of these distribution changes on temperate and subtropical seagrass communities using information derived from invasive species studies. Notably, we outline several scenarios and generate predictions about how their establishment might occur and speculate on impacts of warmer water consumers as they move poleward. We also discuss potential confounding factors of detecting changes in these consumer distributions. Following the invasive species literature, we offer a framework for generating hypotheses and predicting effects from these range-expanding organisms. Given that climates are predicted to continue to warm into the future, thus facilitating additional species expansions, our goal is to guide future research efforts and provide information for rapid dissemination and utility for this growing subdiscipline of marine ecology.